2007
DOI: 10.1002/chem.200601457
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electron Donors on the Radical Polymerization of Vinyl Acetate Mediated by [Co(acac)2]: Degenerative Transfer versus Reversible Homolytic Cleavage of an Organocobalt(III) Complex

Abstract: The molecular structure of bis(acetylacetonate)cobalt(II) ([Co(acac)2]) in solution and in the presence of the electron donors (ED) pyridine (py), NEt3, and vinyl acetate (VOAc) was investigated using 1H NMR spectroscopy in C6D6. The extent of formation of ligand adducts, [Co(acac)2(ED)x], varies in the order py>NEt3>VOAc (no interaction). Density functional theory (DFT) calculations on a model system agree with Co--ED bond strengths decreasing in the same order. The effect of electron donors on the [Co(acac)2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
202
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(211 citation statements)
references
References 54 publications
7
202
2
Order By: Relevance
“…Due to the DMF ligand power, it is likely that DMF molecules coordinate to the free sites of the cobalt complexes, as was demonstrated for pyridine and water. [12,16] Consequently, the CMRP process should be governed only by reversible termination of the propagating chains, as represented in Scheme 1. Under these experimental conditions, the polymerization medium became inhomogeneous and a gray suspension appeared after a few hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the DMF ligand power, it is likely that DMF molecules coordinate to the free sites of the cobalt complexes, as was demonstrated for pyridine and water. [12,16] Consequently, the CMRP process should be governed only by reversible termination of the propagating chains, as represented in Scheme 1. Under these experimental conditions, the polymerization medium became inhomogeneous and a gray suspension appeared after a few hours.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the CMRP of VAc was mainly driven towards a DT mechanism when carried out in bulk, whereas addition of molecules able to coordinate the cobalt, that is, water and pyridine, switched the mechanism towards reversible termination. [12,16] The ability of the CMRP process to provide novel, welldefined, PVAc-containing copolymers of interest was also demonstrated, together with the derivatized PVOH-containing copolymers obtained under basic treatment. The key step of the strategy was the initiation of a co-monomer Abstract: The successful controlled A C H T U N G T R E N N U N G homopolymerization of acrylonitrile (AN) by cobalt-mediated radical polymerization (CMRP) is reported for the first time.…”
Section: Introductionmentioning
confidence: 97%
“…In the case of vinyl esters and some vinyl amides, DFT modeling showed that an extra-stabilization of the CACo bond occurred via an intramolecular chelation of the cobalt atom with the carbonyl function of the last monomer unit and is responsible for the good control observed (Scheme 2) [51,64]. This intramolecular chelation is made possible by the flexible geometry of Co(acac) 2 [67,68] that is not possible for cobalt complexes bearing tetradentate ligands with a rigid square-pyramidal geometry (such as cobalt porphyrins) [55,69,70]. Co(acac) 2 is however less efficient for acrylates polymerization as the result of the low stability of the CACo bond of the dormant species [71].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of neutral ligands, such as pyridine, water, THF, DMF, to the CMRP of vinyl monomers is a route to modulate the reactivity of the cobalt complex and to possibly improve the level of control or the kinetics of the polymerization [52,67,78]. This strategy was used to prepare well-defined block copolymers by sequential OMRP of monomers of different reactivity (Scheme 3, route B).…”
Section: Introductionmentioning
confidence: 99%
“…2 Indeed different types of CRP techniques have been reported which facilitated the synthesis of broad variety of polymeric materials with predetermined molecular weight, narrow MWD and desired chain end groups. CRP was achieved through iniferter (initiation transfer termination), 3 stable nitroxide radicals, 4 triazolinyl radicals, 5 organo-bismuthine, 6 organotellurium, 7 organo-cobalt, 8 organo-stilbene, 9 alkyl-9-BBN, 10 reversible addition-fragmentation-chain transfer (RAFT), 11 degenerative chain transfer by alkyl iodide, 12 and atom transfer radical polymerization (ATRP). 13,14 All the CRP methods include activation and deactivation steps with their respective rate constants, k act and k deact respectively and k deact is higher in all the cases to get controlled radical polymerization of monomers.…”
mentioning
confidence: 99%